Effect of Tithonia diversifolia (Hemsl.) Gray (Giant Mexican Sunflower) on the population of rumen protozoa and methanogens under in vitro conditions - Galindo, Juana; Gonz?lez, Niurca; Sosa, Areadne; Ruiz, Tom?s E.; Torres, Verena; Aldana, Ana Irma; D?az, Humberto; Moreira, Onidia; Sarduy, Luc?a; Noda, Aida C. (Cuban Journal of Agricultural Science, 2011)
The objective of this work was to evaluate the effect of Tithonia diversifolia on the population of rumen protozoa and methanogens under in vitro conditions. The treatments were designed according to the level of T. diversifolia and were: (A) 0 (control); (B) 10 % and (C) 20 %. The rest of the diet consisted of star grass (Cynodon nlemfuensis). The experimental design was completely randomized. The samplings were performed at 0, 2, and 4 hours after the start of the fermentation. The chemical composition of the plant showed the following values: 23.95 % CP, 33.43 % NDF, and 29.54 % ADF. The phytochemical screening proved the presence of tannins and saponins. The population of protozoa was 3.75, 3.25, and 1.5 x 105 cells. mL-1 for A, B, and C, respectively. The methanogenic bacteria were reduced 1.64 and 2.7 folds with 10 and 20 % of T. diversifolia, respectively. The 10 % inclusion activated the population of cellulolytic bacteria although the 20 % did not differ from the control. No effects were found on the population of rumen fungi. It is concluded that Tithonia diversifolia reduces the population of rumen protozoa and methanogens under in vitro conditions. Key words: rumen, Tithonia diversifolia, protozoa, methanogens, cellulolytic bacteria.